Engineering Core-Shell Structures of Magnetic Ferrite Nanoparticles for High Hyperthermia Performance - Mohamed S. A. Darwish; Hohyeon Kim; Hwangjae Lee; Chiseon Ryu; Jae Young Lee; Jungwon Yoon (Nanomaterials, 2020)
Magnetic ferrite nanoparticles (MFNs) with high heating efficiency are highly desirable for hyperthermia applications. As conventional MFNs usually show low heating efficiency with a lower specific loss power (SLP), extensive efforts to enhance the SLP of MFNs have been made by varying the particle compositions, sizes, and structures. In this study, we attempted to increase the SLP values by creating core-shell structures of MFNs. Accordingly, first we synthesized three different types of core ferrite nanoparticle of magnetite (mag), cobalt ferrite (cf) and zinc cobalt ferrite (zcf). Secondly, we synthesized eight bi-magnetic core-shell structured MFNs; Fe3O4@CoFe2O4 (mag@cf1, mag@cf2), CoFe2O4@Fe3O4 (cf@mag1, cf@mag2), Fe3O4@ZnCoFe2O4 (mag@zcf1, mag@zcf2), and ZnCoFe2O4@Fe3O4 (zcf@mag1, zcf@mag2), using a modified controlled co-precipitation process. SLP values of the prepared core-shell MFNs were investigated with respect to their compositions and core/shell dimensions while varying the applied magnetic field strength. Hyperthermia properties of the prepared core-shell MFNs were further compared to commercial magnetic nanoparticles under the safe limits of magnetic field parameters (<5 × 109 A/(m·s)). As a result, the highest SLP value (379.2 W/gmetal) was obtained for mag@zcf1, with a magnetic field strength of 50 kA/m and frequency of 97 kHz. On the other hand, the lowest SLP value (1.7 W/gmetal) was obtained for cf@mag1, with a magnetic field strength of 40 kA/m and frequency of 97 kHz. We also found that magnetic properties and thickness of the shell play critical roles in heating efficiency and hyperthermia performance. In conclusion, we successfully enhanced the SLP of MFNs by engineering their compositions and dimensions.